2015
DOI: 10.1007/s40121-015-0072-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Treatment of Enterococcal Infections with Daptomycin: Insights from a Large European Registry (EU-CORE)

Abstract: IntroductionEvolution of antibacterial resistance in pathogenic enterococcal strains poses a growing therapeutic challenge. Daptomycin, a cyclic lipopeptide, exhibits broad antibiotic activity against Gram-positive bacteria.MethodsThe European Cubicin® Outcomes Registry and Experience, a multicenter, retrospective, non-interventional study, recorded clinical outcomes following daptomycin treatment.ResultsOverall, 472 patients (predominantly elderly Caucasian males) were treated for enterococcal infections. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
(30 reference statements)
1
6
0
Order By: Relevance
“…However, in certain settings daptomycin resistance may be considerably more frequent, as illustrated by a study including 4,274 E. faecium and 7,007 E. faecalis isolates from 19 US hospitals, which found daptomycin resistance among 3.9 and 0.2% of E. faecium and E. faecalis isolates, respectively ( Edelsberg et al, 2014 ). Similar levels of daptomycin resistance in E. faecium were recently reported for a German hospital ( Lübbert et al, 2015 ).…”
Section: Emergence Of Antibiotic Resistance In Enterococcisupporting
confidence: 85%
“…However, in certain settings daptomycin resistance may be considerably more frequent, as illustrated by a study including 4,274 E. faecium and 7,007 E. faecalis isolates from 19 US hospitals, which found daptomycin resistance among 3.9 and 0.2% of E. faecium and E. faecalis isolates, respectively ( Edelsberg et al, 2014 ). Similar levels of daptomycin resistance in E. faecium were recently reported for a German hospital ( Lübbert et al, 2015 ).…”
Section: Emergence Of Antibiotic Resistance In Enterococcisupporting
confidence: 85%
“…However, taking into account the azole resistance rate of 32.9%, significant failure rates of fluconazole-based empirical antifungal therapies for Candida infections have to be considered. It is well known that numerous interventional ERC procedures accompanied by antibiotic therapy predispose for increased antimicrobial resistance in patients with acute cholangitis [ 25 , 27 ], and enterococcal species are often involved in this process [ 42 , 43 ]. Therefore, adequate microbiological diagnosis is essential and should include analysis of the extracted stents.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, most patients were treated with high daptomycin doses (mean 10.125 mg/kg/day). Probably the delayed response observed in previous studies on EIE could be explained by the lower doses used (average dose of 8.5 mg/kg/day) [12], since the use of increased dosage has reported higher and more sustained killing, including for E. faecium [14, 15, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several in vitro studies and some case reports have demonstrated synergistic activity against enterococci with the combination of daptomycin and other antibiotics [10, 11]. Daptomycin at higher doses ranging from 8 to 14 mg/kg/day has been used in EIE with variable and conflicting results, including non-favorable microbiologic and clinical response [1214].…”
Section: Introductionmentioning
confidence: 99%